Characterization of carotid artery plaques using real-time compound B-mode ultrasound - Kern, Rolf; Szabo, Kristina; Hennerici, Michael G.; Meairs, Stephen (Stroke, 2004)
BACKGROUND AND PURPOSE: Real-time compound ultrasound imaging is a new technique for improving the image quality of B-mode scanning. We investigated the value of this method for the characterization of atherosclerotic plaques in the internal carotid artery. - METHODS: Thirty-two patients (22 men, 10 women; mean age, 75 years) with plaques of the internal carotid artery as identified by high-resolution B-mode scanning were investigated with real-time compound ultrasound imaging with the use of a 5- to 12-MHz dynamic range linear transducer on a duplex scanner. Two independent observers rated plaque morphology according to a standardized protocol. - RESULTS: The majority of plaques was classified as predominantly echogenic and as plaques of irregular surface, whereas ulcerated plaques were rarely observed. The interobserver agreement for plaque surface characterization was good for both compound ultrasound (kappa=0.72) and conventional B-mode (kappa=0.65). For the determination of plaque echogenicity, the reproducibility of compound ultrasound (kappa(w)=0.83) was even higher than that of conventional B-mode ultrasound (kappa(w)=0.74). According to a semiquantitative analysis, real-time compound ultrasound was rated superior in the categories plaque texture resolution, plaque surface definition, and vessel wall demarcation. Furthermore, there was a significant reduction of acoustic shadowing and reverberations. - CONCLUSIONS: Real-time compound ultrasound is a suitable technique for the characterization of atherosclerotic plaques, showing good general agreement with high-resolution B-mode imaging. This advanced technique allows reduction of ultrasound artifacts and improves the assessment of plaque texture and surface for enhanced evaluation of carotid plaque morphology.
Gesehen am 23.05.2022